Eksistensi Tuan Guru Sebagai Rujukan Bimbingan Konseling di Tengah Pandemi Covid-19 - sukardiman, sukardiman (Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstrakCounseling guidance in the midst of a pandemic is urgently needed to awaken individuals who are simplistic (underestimate) against government regulations regarding health protocols that must be applied for the common good. In overcoming this problem, Tuan Guru as a role model in the Sasak communityis very much needed, in order to prevent the consequences that can be caused by a handful of people who do not obey and obey government regulations and appeals, so that the rete of the spread of covid-19 can decrease, even stop. Tuan Guru has the potential and capital to provide religious counseling, namely Tuan Guru has the legitimacy of religious language, where with his religious knowledge they are able to direct the community. Inherent in their personal qualities, so that they become role models for society. This is very much needed by the government, because it can be a positive bridge to avoid miscommunication.Key Word: Counseling Guidance, Tuan Guru, and Covid-19